The impacts of overseas M&A on shareholder wealth: evidence from Chinese listed companies - LIANG, SICHENG (2018)
The recent review of literature on M&A focuses on two issues: firstly, whether the borderline M&A made by Chinese companies can create shareholder prosperity; secondly are the factors that influence the prosperity of cross-border M&A. This paper will examine the influence of cross-border M&A on shareholder wealth of listed Chinese companies during the process when they seek their way of development, as well as make a systemic and multivariate analysis of the influencing mechanism. The cross-border M&A created by Chinese A-share listed firms Shenzhen and in Shanghai stock exchange market from 2003 to 2017 are used as samples, and the event survey is used in the evaluation of cumulative abnormal return as well as the chosen firms in the event window. A multiple regression analysis will be used to evaluate the factors that affects wealth at a cross-border M&A in relation to nation, industry and company. The empirical study shows that Chinese companies' cross border M&A will generate substantial and optimistic cumulative abnormal return, which shows that the stock market and the investors holds a positive attitude towards M&A. Cross-border M&A shall still be a strategic choice for Chinese companies to implement the "going-out" strategy, enhance their market power, reduce costs, and enhance global competitiveness. The multiple regression model results indicate a positive correlation between the investors' attitude towards the cross-border M&A and the host country's free economic system, the host company's diversified structure, the scale of M&A and their rich international experience. While, a developed host country, a related industry, the high-tech industry, the company scale, the M&A experience of the host country and its governance will have a undesirable effect on its fortune result.